(untitled) (University of Khartoum Engineering Journal, 2022)
Nowadays, traffic congestion is a serious problem; it wastes people’s time, increases collision rate, delays emergency and contributes in environment pollution. This paper aims to reduce these effects and enhance road traffic infrastructure by using video cameras to monitor the streets, the video is processed to estimate traffic density then traffic status stored in web database and updated continuously. Users can easily install the developed android application, indicate their destination and in time, three optimum routes based on the traffic volume are shown on the map. This technique was shown to be an effective way in reducing traffic congestion and enhancing roads traffic.